Peran Data dan Informasi dalam Teori Sistem Organisasi - Rheina Sayla; Dinda Putri; Muhammad Arby Fahrezi; Abdul Fattah Nasution (Student Scientific Creativity Journal, 2025)
Data and information play a strategic role in organizational systems theory, particularly in supporting fact-based decision-making processes. In this theory, organizations are viewed as open systems that continuously interact with their environments. Data serves as raw material that, through analysis, is transformed into actionable information to understand the internal and external dynamics of organizations. Accurate and relevant information helps organizations manage complexity, identify opportunities, and address challenges in ever-changing environments. The data management process encompasses collection, storage, analysis, and distribution, enabling integration across organizational units and enhancing synergy. Additionally, information-based feedback systems are vital for measuring organizational performance and driving continuous innovation. The effective use of data and information not only improves operational efficiency but also supports strategic planning and adaptation to market changes. In the context of digitalization, the role of data and information has become increasingly critical, as technology enables the processing of large-scale data more quickly and accurately. This article explores how data and information, as core components of organizational systems theory, can be utilized to create added value and support organizational sustainability in the modern era.